Tellurization of Pd(111) revisited: Formation of a TePd2 surface alloy but no PdTe2 monolayer - Engel, Eric; Wegerich, Alexander; Raabgrund, Andreas; Schneider, M. Alexander (Surface Science, 2024)
In a recent publication [2D Materials, 8, 045033 (2021)], it was reported that the growth of a monolayer PdTe2 in ultra-high vacuum could be achieved by deposition of tellurium on a palladium (111) crystal surface and subsequent thermal annealing. By means of low-energy electron diffraction intensity (LEED-IV) structural analysis, we show that the obtained 3×3R30° superstructure is in fact a TePd2 surface alloy. Attempts to produce a PdTe2 layer in ultra-high vacuum by increasing the Te content on the surface were not successful.
CRIS-Team Scopus Importer:2024-06-14
Keywords: LEED-IV; Palladium; Structural analysis; Surface alloy; Tellurium; Transition metal dichalcogenide